SOIL ALKALINITY CONTROL USING THREE DIFFERENT BIO-MATERIALS (WASTES) FOR SOIL SUSTAINABILITY AND PRODUCTIVITY - CHIWETALU, UCHE; Ogbuagu, Nneka, Juliana; Okechukwu, Michael Emeka (FUDMA JOURNAL OF SCIENCES, 2021)
The study presents soil alkalinity control using three different bio-materials for soil sustainability and productivity. It has been noted that soils without balanced pH have trouble with nutrient solubility, thereby making soil nutrients unavailable for plants. 5kg soil sample was measured and put in five different containers. Thereafter, 450g of ash was added to four containers to induce alkalinity. Moreover, three samples were further mixed with 3 different treatments; treatment A, B and C. In all, five samples were set for the study, sample A (control or ordinary soil), B (soil + ash), C (soil + ash + poultry droppings), D (soil + ash + cassava peals) and E (soil + ash + dry grasses). pH tests’ were conducted weekly on the samples and the results subjected to ANOVA test. Results obtained were 7.2, 11.5, 9.5, 8.7 and 9.2 for samples A, B, C, D and E respectively in week 1. Similarly, 7.2, 11.5, 8.4, 8.2 and 9.0; 7.2, 11.5, 7.8, 7.9 and 8.7; 7.2, 11.53, 7.4, 7.5 and 8.2 for samples A, B, C, D and E were obtained in 2nd, 3rd and 4th week respectively. The results showed that the treatments have significant effect in reducing alkalinity (p = 5%).